PELUANG INVESTASI USAHA BUDIDAYA KUTU LAK (Laccifer lacca Kerr): STUDI KASUS DI KPH PROBOLINGGO PERUM PERHUTANI UNIT II JAWA TIMUR - Ira Taskirawati; F. Gunawan Suratmo; Dudung Darusman; Noor Farikhah Haneda (PERENNIAL, 2008)
Lac insect (Laccifer lacca Kerr) is phytophogus insect, that feed on Kesambi Tree (Schleichera oleosa Merr). During its life cycle, lac insect has been producing secretion in liquid form, known as LAK and having many uses, such as varnish/polish, food cover, drug capsule, cassette ribbon, etc. In 2005, Perum Perhutani has produced 60.547 kg LAK pellets, but has not fulfilled yet market demand. Cultivation technique is still conducted in a very sampling, and easy to be studied. Investment in developing lac insect is also profitable, and promising. There are two choices of management schemes in it cultivate, the first is by infecting lac insect to the host tree when the tree is 15 years old (project I) and the second is by infecting lac insect when the tree is 4 years old (project I). Financially, the Project II is more beneficial than Project I, so that the investment for project II is reasonable to be done. The value of NPV+22.321.052.395, IRR 16.9%, BCR 1.55 and Net B/C 3.71 with discounted payback period for 10 year 8 months. Key words: Laccifer lacca Kerr, Schleichera oleosa Merr, investment opportunity, strategy in developing